Steve S. answered • 02/09/14

Tutoring in Precalculus, Trig, and Differential Calculus

6p^2 - 42 = 72

Add 42 to both sides:

6p^2 = 42 + 72 = 114

Divide by 6 both sides:

p^2 = 19

Take square root of both sides:

|p| = √(19)

p = ±√(19)

Roseland W.

asked • 02/09/146p is squared. I know the answer is 4,3 could you help me under stand how to work the problem out. Thank you

Follow
•
4

Add comment

More

Report

Steve S. answered • 02/09/14

Tutoring in Precalculus, Trig, and Differential Calculus

6p^2 - 42 = 72

Add 42 to both sides:

6p^2 = 42 + 72 = 114

Divide by 6 both sides:

p^2 = 19

Take square root of both sides:

|p| = √(19)

p = ±√(19)

James P. answered • 02/09/14

Experienced Math Tutor

Hi Roseland,

I want to try and answer your question here. Just to make sure the question is...

6(p)^{2 }- 42 = 72 solving for p.

So, there are many ways to solve this problem. The first method is to subtract 72 to both sides of the equation.

6(p)^{2 }- 42 - 72 = 0 --> This leads to --> 6(p)^{2 }-114 = 0 --> Now you want to factor 6 from both terms (the 6(p)^{2} term and the -114 term) --> This gives us...

6(p^{2} -19) = 0 --> divide by 6 to the whole equation --> 6(p^{2} -19)/6 = 0/6 --> 6(p^{2} -19)/6 = 0/6 --> this gives us...

(p)^{2 }- 19 = 0 --> add 19 to both sides of the equation --> (p)^{2 }-19+19=0+19 --> (p)^{2} = 19 --> take the square root of both sides of the equation to obtain the value of p.

p=(19)^{1/2} --> **p = 4.3588**

I hope this helped. Let me know if you have any questions about this solution.

Vivian L. answered • 02/09/14

Microsoft Word/Excel/Outlook, essay composition, math; I LOVE TO TEACH

Hi Roseland;

6p^{2}-42=72

Let's subtract 72 from both sides...

6p^{2}-42-72=72-72

6p^{2}-114=0

Let's factor-out the 6...

6(p^{2}-19)=0

The parenthetical equation must equal zero. Therefore...

p^{2}-19=0

(p+√19)(p-√19)=0

Let's FOIL...

FIRST...(p)(p)=p^{2}

OUTER...(p)(-√19)=-p√19

INNER...(√19)(p)=p√19

LAST...(√19)(-√19)=-19

p^{2}-(p√19)+(p√19)-19=0

p^{2}-19=0

(p+√19)(p-√19)=0

Either or both parenthetical equations must equal zero...

p+√19=0

p=-√19

p-√19=0

p=√19

The square root of 19 is approximately 4.3.

Ask a question for free

Get a free answer to a quick problem.

Most questions answered within 4 hours.

Find an Online Tutor Now

Choose an expert and meet online. No packages or subscriptions, pay only for the time you need.